2010
DOI: 10.1016/j.ijpharm.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-conjugated lipid-coated PLGA nanoparticles for targeted delivery of aromatase inhibitor 7α-APTADD to breast cancer cells

Abstract: Transferrin (Tf)-conjugated lipid-coated poly(d,l-lactide-co-glycolide) (PLGA) nanoparticles carrying the aromatase inhibitor, 7α-(4′-amino)phenylthio-1,4-androstadiene-3,17-dione (7α-APTADD), were synthesized by a solvent injection method. Formulation parameters including PLGA-to-lipid, egg PC-to-TPGS, and drug-to-PLGA ratios and aqueous-to-organic phase ratio at the point of synthesis were optimized to obtain nanoparticles with desired sizes and drug loading efficiency. The optimal formulation had a drug loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 28 publications
5
66
0
Order By: Relevance
“…[ 4,8 ] Both SKBR3 and MDA-MB-231 cells possess high levels of TfR1 [ 33 ] which would assist cellular uptake of H-AFt-encapsulated-Gefi tinib. [ 34 ] The greater SKBR3 growth inhibition by H-AFt compared to MDA-MB-231 implies greater sequestration of H-AFt by SKBR3 cells. Indeed, it has been shown previously that ferritin was not taken up by MDA-MB-231 cells.…”
Section: Communicationmentioning
confidence: 98%
“…[ 4,8 ] Both SKBR3 and MDA-MB-231 cells possess high levels of TfR1 [ 33 ] which would assist cellular uptake of H-AFt-encapsulated-Gefi tinib. [ 34 ] The greater SKBR3 growth inhibition by H-AFt compared to MDA-MB-231 implies greater sequestration of H-AFt by SKBR3 cells. Indeed, it has been shown previously that ferritin was not taken up by MDA-MB-231 cells.…”
Section: Communicationmentioning
confidence: 98%
“…These results suggest that the aromatase inhibition activity of the transferrin nanoparticles was enhanced relative to that of the nontargeted nanoparticles, which was attributable to transferrin receptor-mediated uptake. 132 The α v β 3 integrin is an endothelial cell receptor for extracellular matrix proteins harboring the arginine-glycine-aspartic acid (RGD) sequence. 126 Wang et al conjugated doxorubicin to PLGA, and the nanoparticle surfaces were then linked with PEG and the RGD peptides to achieve both passive and active targeting functions.…”
Section: Ligand-receptor Interactionmentioning
confidence: 99%
“…PLGA NPs loaded with the 7 -APTADD were significantly more effective preventing proliferation of the human breast cancer cell line SK-BR-3 than non-targeted NPs. These results suggested that the aromatase inhibition activity of the Tf-NPs was enhanced relative to that of the non-targeted NPs, which was attributable to TfR mediated uptake [87] Gan and coworkers observed that Tf-conjugated poly(lactide)-D--tocopheryl polyethylene glycol succinate diblock copolymer NPs loaded with Dtxl could be more efficient eliciting cytotoxicity against C6 glioma cells than other nontargeted formulations [88].…”
Section: Transferrin Receptormentioning
confidence: 98%